Book Review: International Hand-Book on Tourism and Peace (Journal of Tourism and Hospitality Education, 2018)
Not available. About book :Edited by : Cordula Wohlmuther and Werner WintersteinerPublisher : Centre for Peace Research and Peace Education of KlagenfurtUniversity, AustriaYear of : 2014PublicationISBN No. : 978-3-85435-713-1Journal of Tourism and Hospitality Education 8 (2018) 97-106